Regional Economic Interation and Impacts on Growth, Poverty and Income Distribution - The Case of Thailand - Nguyen, Tien Dung (ĐHKT, 2016)
Trade liberalization and regional economic integration have recently accelerated in East Asia, where several free trade areas have been established or are under negotiation. Vietnam, after acquiring Association of Southeast Asian Nations membership in 1995, has signed a bilateral trade package with the United States and participated in the China-ASEAN free trade area. This paper attempts to analyze the impact on Vietnam of ongoing regional economic integration, focusing on growth, poverty reduction and income distribution.